Understanding The State of Emergency - Wan Ahmad Fauzi, Wan Husain (RTM, 2021)
MOMENTUM (WHAT MATTERS) : UNDERSTANDING THE STATE OF EMERGENCY WITH DATO' WAN AHMAD FAUZI WAN HUSAIN DATE : 17TH FEBRUARY 2021, WEDNESDAY | TIME: 11:15 AM | VENUE: FB LIVE TRAXX FM